Interdisciplinary treatment of Class II malocclusion with severe periodontitis - Prof Hsiang-hua Lai (Elsevier, 2023)
Introduction: The interdisciplinary treatment of a Class II malocclusion patient with severe periodontitis by using temporary anchorage devices, large overjet and deep overbite is corrected and proper occlusal function has been re-established. Case Description: A 54-year-old female suffered from severe periodontitis, pathological tooth migration and multiple missing teeth asked for full mouth rehabilitation. Class II division 1 malocclusion with large overjet and deep overbite with exaggerate curve of Spee in the lower arch was observed. She also exhibited convex profile with retruded chin and lip protrusion. The treatment strategy included extraction of upper right second premolar, upper left first premolar, and poor prognosis upper right second molar. With the aid of skeletal anchorage in the upper posterior region and early application of reverse rectangular NiTi wire in the lower arch, the large overjet and deep overbite has been corrected. Discussion: Orthodontic treatment in adult patient may be complicated by preexisting pathological conditions and required close cooperation between different specialist. With well-controlled orthodontic force magnitude and direction, the flared upper incisors have been retracted without any further threats on periodontium. Even more, providing a more favorable environment for periodontal maintenance. Normal overjet and overbite with stable occlusion was established, and significant improvement in facial profile was achieved. Conclusion: This case demonstrates the effectiveness of interdisciplinary orthodontic treatment in patients with severe periodontitis and pathological tooth migration.